Pengaruh Kualitas Corporate Governance Terhadap Cost Of Equity Perusahaan Manufaktur Di Indonesia - Fiki Kartika (Jurnal Solusi, 2018)
This research aims to determine the impact of Good Corporate Governance (GCG) on the cost of equity for manufacturing companies in Indonesia. The sampling technique uses purposive sampling, namely companies listed on the Indonesia Stock Exchange. The analysis was carried out in the Manufacturing industry sector in 2013 - 2015. The GCG index was measured using five dimensions adopted from Black et al. (2003) and Cost of Equity is measured by the ex ante cost of equity capital using the Price Earning Growth (PEG) proxy. The reason for using ex ante cost of equity capital is ex-ante is more describing the role of investors in seeing the risk of a company. The results of this study indicate that GCG negatively affects on the cost of equity. GCG limits managerial opportunism and reduces agency conflicts between owners and agents. Therefore, shareholders are willing to accept a lower risk premium, effectively reducing equity costs.